PELATIHAN PEMASARAN ONLINE UNTUK PRODUK PRODUK UNGGULAN BAGI PKK DAN KADER POSYANDU DI DESA KARYAMEKAR, GARUT, JAWA BARAT - Ramadhani Hamzah; Rina Nurhayati; Jalaludin, Jalaludin; Astuti, Enny Diah; Maulida, Sofia (JURNAL ABDIMAS PLJ, 2025)
Online marketing training for PKK (Family Welfare Movement) and Posyandu (Integrated Service Post) cadres' flagship products aims to increase sales and expand market reach through digital platforms such as social media and e-commerce. This training equips participants with basic digital marketing skills, business account optimization, engaging content creation, and the use of applications such as e-commerce and marketplaces. Furthermore, this activity also improves digital literacy and empowers families and communities economically. This community service program aims to provide online marketing training for PKK women as a continuation of the creative economy program in Karyamekar Village, Garut, West Java. The community service event was held on November 14-15, 2025, in the Karyamekar Village Hall. The method used was presentations, discussions, and a question-and-answer session. During the presentation, the speaker discussed the importance of digital marketing in marketing products. With the advancement of technology, digital marketing is essential for product marketing. Online marketing can transcend the boundaries of time, space, and location, meaning sales can be made anytime and anywhere. A strategy is needed to leverage digital marketing to increase sales.